Visual preference dimensions of historic urban areas: the determinants for urban heritage conservation - Najd, Meysam Deghati; Ismail, Nor Atiah; Maulan, Suhardi; Mohd Yunos, Mohd Yazid; Niya, Mahsa Dabbagh (Pergamon Press, 2015)
Challenges between urban development and heritage conservation are more critical in developing countries since new constructions threaten historic urban areas. On account of vast developments in urban areas, the so-called cultural heritage of cities, may tolerate irreversible damages, thus striking a balance is essential. The opinions of stakeholders could be a reliable reference in maintaining this balance. Therefore, the perception of the public should complement the expertise required in the conservation of historic urban areas and the development of adjacency. This paper outlines the findings of a study conducted to identify visual preferences of international tourists toward the historic centre of Kuala Lumpur as a way of passive participation. Thanks to environmental psychology and by means of an in-situ photograph-based survey, six visual preference dimensions were recognized that influence the perception of tourists towards the study area. In the current study, these dimensions are entitled visual chaos, urban greenery, roadside heritage, historic architecture, connectivity and modernity. Each one of these dimensions contains influential elements and features. “Content Identifying Method” carried out to identify the favourable and repulsive contents resulted in high or low preferability of each preference dimensions, respectively. It is concluded that, the surroundings of historic settings show the most neglect from conservation.